A study on the credit policy practice by Professional Services Development Corporation (PSDC) in account receivable management / Siti Nadrah Sh Mohd Afandi - Sh Mohd Afandi, Siti Nadrah (2010)
Professional Services Development Corporation Sdn Bhd (PSDC) is company that serve world class professional service providers trough promoting professional overseas, building the capacity and capability of our professionals, advocating for professionals and provision of an information centre on and for professionals. PSDC in Malaysia is operated at level 24, Maju Tower, 1001 Jln Sultan Ismail, 50250 Kuala Lumpur. PSDC also was incorporated by Minister of Finance Incorporated (MOF Inc) as a private limited company and also established to accelerate the capacity of Malaysian professional service providers. As we can see from the other firm, PSDC also facing a problem about credit risk equally as compared to its competitor. This is why the credit policy is need in any recognized firm to maintain and generate their business as well to keep the cash flow move. A high collection period shows a high cost in extending credit to customer. PSDC Sdn Bhd has some weakness in implement the credit policy to the company. Usually they not will grant the credit to their customer without know about the financial background of the company. Furthermore, for credit collection policy, PSDC Sdn Bhd have not enough staff to control and sometimes some cases are keep own settlement even they pay late or sometimes not paid at all. In addition, the company should attract their customer by apply the credit term because it also can benefit the customer also to pay by giving a discount when they pay within the period. Other than that, the company does not apply the average collection period (ACP) in order to evaluate the company performance in term of collection year by year.